Tuberculosis control in the face of emerging infectious diseases: Highlights from the 7th South African Tuberculosis Conference - Shamsuddeen Yusuf Ma'aruf; Tayla Smith; Su‐Mari du Plessis; Zimvo Obasa (Wiley, 2023)
Abstract Tuberculosis (TB) remains a disease of global concern caused by the pathogen Mycobacterium tuberculosis. In the face of emerging infectious diseases, such as COVID‐19, dengue fever, Lassa fever, and Ebola, attention to the control of TB is losing its place as a priority in public and global health initiatives. Recently, after a hiatus enforced by the COVID‐19 pandemic, scientists, public health experts, and other stakeholders met in Durban, South Africa (SA) for the 7th South Africa Tuberculosis Conference to share, discuss, and recommend strategies to regain TB control. In this paper, we summarized and captured key plenary sessions and presentations by scientists and other stakeholders at the conference, which focused on various themes: pathogenesis of TB-pathogen and host, drugs/vaccine/diagnostics, implementation/health systems, and social and community aspects of TB. The current policy and effort to control TB have declined in recent times. We suggested a critical and inclusive engagement of funders, researchers, policymakers, and the civil society toward regaining TB control. Additional investigation into this paper may make it easier to identify control strategies to help realize the End TB Strategy.